The cost of knowing - Morris, Brittney (Simon & Schuster BFYR, 2021)
Sixteen-year-old Alex Rufus's curse of seeing the future distracts him from being and doing his best, but when he sees his little brother Isaiah's imminent death, he races against time, death, and circumstances to save him.